NETRALITAS KEPALA DESA DALAM PILKADA: SEBUAH TINJAUAN HUKUM YANG KOMPREHENSIF - Harmono; Suwarsono, Hendri; Abdulah Pakarti, Muhammad Husni (Jurnal Keadilan Pemilu, 2024)
Local Elections (Pilkada) in Indonesia are pivotal in the democratic framework, requiring fair and transparent conduct at all levels of local government, including villages. Village Heads play a crucial role in upholding the integrity of the electoral process and ensuring its adherence to principles of healthy democracy. Village heads play a pivotal role in local governance in Indonesia, responsible for administering government affairs, development initiatives, and public services within their communities. However, the issue of village head neutrality becomes crucial in the context of regional elections. This study aims to examine the role of Village Heads in facilitating the smooth conduct of Pilkada, particularly in the context of implementing neutrality regulations. These regulations are stipulated in Law Number 23 of 2014 on Regional Government.The research methodology employed involves a literature review from various relevant sources, including legislative regulations, research reports, and relevant case studies. The analysis reveals that despite the existence of neutrality regulations, challenges persist in their practical implementation. Some Village Heads occasionally engage in non-neutral political activities, directly or indirectly influencing the overall electoral process. The impact of Village Heads' neutrality violations on the integrity of the democratic process at the village level includes election unfairness, loss of public trust in the local democratic system, and potential social polarization and conflicts. Efforts to enhance Village Heads' understanding and compliance with neutrality regulations, such as training, intensive socialization, and monitoring and addressing violations, need continuous improvement. This research aims to contribute to improving the local democratic system in Indonesia by strengthening the role of Village Heads as guardians of neutrality in the electoral process.